The effect of smallholder maize farmers’ perceptions of climate change on their adaptation strategies: the case of two agro-ecological zones in Ghana - Danley Colecraft Aidoo (Elsevier, 2021)
Maize is one of the most common cereals and a major staple that is cultivated across all agro-ecological zones in Ghana. However, maize productivity is affected by changes in climate, such as increased temperature and variations in rainfall. These changes in climate require farmers to implement practices (adaptation strategies) in order to reduce the magnitude of crop losses. This study examined how the perceptions of maize farmers regarding climate change affect their choice of adaptation strategies. A mixed methods approach was adopted for the study. Data was collected by means of a survey of 386 maize farmers along with focus group discussions. Quantitative data were analysed with descriptive statistics, Principal Component Analysis (PCA) and multivariate probit regression, while qualitative responses were used to explain the findings. Results from the data analysis indicated that maize farmers employed 17 adaptation strategies in adapting to climate change. The most common strategies identified were change of planting days, crop diversification, use of resistant varieties, and monitoring weather forecasts on radio. Furthermore, the factors that influenced the choice of adaptation strategies by maize farmers in both zones were experience in farming, household size, and perceptions about the impact and intensity of climate change.